A qualitative approach – delineates changes on pubertal body image after menarche. Issue 1 (31st December 2022) - Riboli, Greta; Borlimi, Rosita; Caselli, Gabriele
ABSTRACT: The present study explored young adolescent's (female at birth) experiences with their bodies following pubertal changes. Twenty-seven participants selected from a parent-daughter workshop at school who had experienced 1 to 6 menstrual cycles were interviewed. Data were collected and analysed using interpretative phenomenological analysis. Four current themes emerged from the analysis: (i) perception of body changes in puberty; (ii) intense emotions; (iii) managing body changes and secondary sexual characteristics; (iv) a new way of experiencing the body. Results support an integrative approach to the prevention of body negative image. Based on these findings, it is important to considered body image in the complexity of its emotional, cognitive and behavioural manifestations in order to promote psycho-educational programmes related to secondary sexual characteristics, consistent with the needs of today's pubertal female at birth.